Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
=> -5 + x - 10 + 4 = -5 + x - 10 + 4
= -5 + x - 10 + 4 + 5 - x + 10 -4
= [( - 5 ) + 5] + [x + (-x)] + [(-10) + 10] + [4 + (-4)]
= 0 + 0 + 0 + 0
HỌC TỐT !
[url=http://Blog.Uhm.vN][img]http://blog.uhm.vn/emo/bobototo/44.gif[/img][/url]
\(A=\dfrac{2^{20}\cdot3^{10}\cdot35+2^{10}\cdot65+2^2\cdot3^2\cdot2^{12}\cdot3^6\cdot3^2\cdot5^2}{2^{12}\cdot5^4}\)
\(=\dfrac{2^{10}\left(2^{10}\cdot3^{10}\cdot35+65+2^4\cdot3^{10}\cdot5^2\right)}{2^{12}\cdot5^4}\)
\(=\dfrac{1}{4}\cdot\dfrac{2^4\cdot3^{10}\cdot5\cdot\left(2^6\cdot7+5\right)+65}{5^4}\)
\(=\dfrac{1}{4}\cdot\dfrac{2^4\cdot3^{11}\cdot5\cdot151+65}{5^4}\)
\(=\dfrac{1}{4}\cdot\dfrac{2^4\cdot3^{11}\cdot151+13}{5^3}=\dfrac{2^4\cdot3^{11}\cdot151+13}{500}\)
Tử số : \(4^5.9^4-2.6^9\)
\(=\left(2^2\right)^5.\left(3^2\right)^4-2.2^9.3^9\)
\(=2^{10}.3^8-2^{10}.3^9\)
Mẫu số : \(2^{10}.3^8+6^8.20\)
\(=2^{10}.3^8+2^8.3^8.2^2.5\)
\(=2^{10}.3^8+2^{10}.3^8.5\)
\(=2^{10}.3^8.6\)
\(\frac{2^{12}.13+2^{12}.65}{2^{10}.104}+\frac{3^{10}.11+3^{10}.5}{3^9.2^4}\)
\(\Rightarrow\frac{2^{12}.\left(13+65\right)}{2^{10}.104}+\frac{3^{10}.\left(11+5\right)}{3^9.2^4}\)
\(\Rightarrow\frac{2^{12}.78}{2^{10}.104}+\frac{3^{10}.2^4}{3^9.2^4}\)
\(=\frac{2^2.3}{4}+3\)
\(=3+3=6\)
thực hiện biến đỏi ta có :